Enhancing climate adaptation through iSAT: A Climate-Informed Agro-Advisory Tool - Emanuel, Jacob; Whitbread, M Anthony; Akinseye, M Folorunso; Dhulipala, Ram; Worou, Nadine; Faye, Aliou; Kebe, Ndeye Amy; Seck, Babacar; Konte, Oumar; Rötter, P Reimund (International Livestock Research Institute, 2024)
This presentation focuses on iSAT, an intelligent agri-advice tool designed to help farmers better manage climate risks and improve their farming practices using climate and agronomic data. Initially developed as a seeding application, iSAT offers strategic and tactical advice before and during the agricultural season. The presentation highlights its deployment in Senegal, where it has benefited 4,000 farmers directly and over 200,000 indirectly via radio broadcasts, demonstrating its positive impact on agricultural yields and climate adaptation.